EXPERIMENTAL STUDY ON MECHANICAL PROPERTIES OF ALUMINUM ALLOY WELDED STRUCTURE - ZHANG Ming; FANG YanHua; FANG ZiFan; KONG Bo; WU ZuShuang; ZHAO GuangWei (Jixie qiangdu)
Taking the aluminum alloy welded structure as the research object,the mechanical test and finite element analysis were used to study the performance of the welded structure. Four kinds of aluminum alloy materials,5083,6061,6063 and 6082,were selected for TIG welding,Through tensile test,hardness test and finite element analysis,four kinds of aluminum alloy materials,I-groove and V-groove,ER-5356 and ER-5087 welding wires,single lap and double lap connection methods and their welding processes are co MPared. A section of tower structure compression test is carried out. The results show that the welding properties of ER-5356 and ER-5087 are similar,V-groove and double lap welding are the best. The yield strength and tensile strength of 6061 aluminum alloy welding structure are 202 MPa and 290 MPa. The maximum allowable stress of a section of tower body is 60% of that of aluminum alloy welded structure. This research work lays a foundation for further exploring the application of aluminum alloy welded structure in transmission tower structure.